Strategies for pain management: a review - Sollami, Alfonso; Marino, Leonardo; Fontechiari, Simona; Fornari, Marta; Tirelli, Pierangela; Zenunaj, Elisabetta (Acta Biomedica Atenei Parmensis, 2015)
Problem/Background: Pain management is a major worldwide health problem. It manifests itself in a variety of forms involving in turn a multiplicity of responses and therapeutic strategies. Following from this, the training of health personnel must deal with this situation and must not only offer technical assistance, but must also deal with the psychological and social aspects of the problem. In recent years various guidelines and protocols have become popular for pain management. The aim of this paper is to present a literature review of the major international databases. Type of research: Systematic review. Objective: To identify relevant studies in the literature on pain management and identify the guidelines recognized by the scientific community. Materials and methods: A literature search was conducted using the keywords “pain management” and “nurse” published since 2000 in English and Italian in the following databases: PubMed, CINAHL, Med Line. Excluding items which did not meet the inclusion criteria, 49 articles were included in the review. Results: Despite a growing availability of evidence-based guidelines, drugs for pain control and the enactment of legislation to promote the use of opioid analgesics in pain therapy, a substantial proportion of the European population continues to have pain. Estimates of the prevalence of pain symptoms in the literature show that between 40% and 63% of hospitalized patients reported pain, peaking at 82.3% in cancer patients in advanced stages of the disease or terminally ill (in hospital or at home). Several studies published in recent years have agreed on a definition of some key points in the management of pain. Studies agree that pain should be recognized as the 5th vital sign, hence the need for validated scales whether single or multi-dimensional, quantitative or qualitative. The approach to the management of pain must be multi-professional, and the use of pharmacology must be in accordance with the WHO three-step approach. Several studies have demonstrated that communication and training of operators, associated with accurate information to patients, are effective elements to improve health care delivered to patients. These studies have led to the publication of guidelines by various scientific societies, indicating timely strategies for effective pain management both in hospital and in the territory. A possible development of this research could be to conduct a retrospective study in accordance with the AUDIT methodology so that we can check the implementation of guidelines and propose corrective actions to meet the defined standards.